2022
DOI: 10.3390/antibiotics11101425
|View full text |Cite
|
Sign up to set email alerts
|

Thermoplastic Starch Composites Reinforced with Functionalized POSS: Fabrication, Characterization, and Evolution of Mechanical, Thermal and Biological Activities

Abstract: Rapid advancements in materials that offer the appropriate mechanical strength, barrier, and antimicrobial activity for food packaging are still confronted with significant challenges. In this study, a modest, environmentally friendly method was used to synthesize functionalized octakis(3-chloropropyl)octasilsesquioxane [fn-POSS] nanofiller. Composite films compared to the neat thermoplastic starch (TS) film, show improved thermal and mechanical properties. Tensile strength results improved from 7.8 MPa to 28.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…E. coli was negatively charged and had less surface area than S. aureus . Furthermore, based on the observations, the PBMS-3 composite film exhibited strong antimicrobial activity against S. aureus and E. coli than the other films [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…E. coli was negatively charged and had less surface area than S. aureus . Furthermore, based on the observations, the PBMS-3 composite film exhibited strong antimicrobial activity against S. aureus and E. coli than the other films [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Prior to use, the PBAT pellets were dried in an oven for 24 h at 60 °C. The PBAT composites are prepared using the solution mixing and drop-casting method [ 34 , 35 ]. After dissolving 2.0 g of PBAT in chloroform, the estimated amount of AgSnO 2 was added.…”
Section: Methodsmentioning
confidence: 99%
“…After 12 h, the stirred solutions were cast onto a glass plate and sonicated for 30 min to produce PBAT/AgSnO 2 (ACP) composites. The antimicrobial properties of the solvent were evaluated by allowing an additional 24 h to dry at room temperature [ 35 ]. ACP-0.0, ACP-0.5, ACP-1.0, ACP-2.0, ACP-3.0, and ACP-5.0, respectively, are abbreviations for PBAT and PBAT/AgSnO 2 composite film of 0.5, 1.0, 2.0, 3.0, and 5.0 weight %.…”
Section: Methodsmentioning
confidence: 99%
“…Because of its hydrophobicity, POSS significantly increased the antibacterial activity of the nanofiber membranes. Venkatesan et al 29 added functionalized POSS nanoparticles to thermoplastic starch. Their results demonstrated that incorporating functionalized POOS enhanced the antimicrobial action of the thermoplastic starch against S. aureus and E. coli bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its hydrophobicity, POSS significantly increased the antibacterial activity of the nanofiber membranes. Venkatesan et al 29 As POSS content increased, the antibacterial capabilities of modified PP fibers improved. Moreover, Wang et al 32 observed that the PLA matrix was reinforced by the addition of 7.5 wt% of trisilanolisobutyl-POSS.…”
mentioning
confidence: 99%